The importance of Ethiopian soils in irrigation and overall watershed management [Abstract only] - Schmitter, Petra S.; Haileslassie, Amare; Nakawuka, Prossie; Gebregziabher, Gebrehaweria; Tesema, M.; Tegegne, D.; Abdela, M.; Yilak, Debebe L.; Tilahun, S.; Ayana, M.; Langan, Simon J. (2016)
Irrigation has a large potential to increase agricultural output and yield per unit area. However, the long term sustainability increased production, together with degradation of the soils (and associated water bodies) in irrigated areas may be irreparably damaged by inappropriate watering schedules. In Ethiopia, surface and groundwater irrigation has been promoted intensively throughout the country. While many projects focus on individual or scheme level water access, very little is known about the sustainability of irrigation in Ethiopia. Aside, from water quantity the quality of irrigation water has a significant impact on soil stability and its chemical properties. In the Ziway, a very important irrigation area in Oromia, soils are increasingly becoming sodic due to the large irrigation quantities and the poor water quality. The International Water Management Institute focusses through various research for development projects on improving irrigation water management, increasing groundwater recharge and assessing the environmental impact of irrigation for various soils throughout the Amhara, Oromia and SNNPR region. Irrigation scheduling tools have been introduced at individual and scheme based small holder farms for the irrigation of high value horticultural and fodder crops to improve water and crop productivity and reduce nutrient leaching. Simultaneously groundwater recharge experiments were carried out using deep tillage and soil & water conservation practices in the rainy season. In these studies, soils are sampled, irrigation quantified, soil moisture measured and standard agronomic practices monitored. Additionally, socio-economic data are being collected on household composition, land holding, labor involved in as well as income generated by the various technologies. Preliminary results showed that crop productivity was not effect while reducing water between 18-35% as function of the prevailing soil types. For the groundwater recharge studies lowest runoff values and highest crop productivity values were observed in the deep tillage plots compared to zero and normal tillage. The socio-economic as well as biophysical data are used in field as well as watershed models to assess the environmental and economic impact of various irrigation scenarios throughout the agro-ecological zones.